Manajemen Gerakan Literasi Al-Qur'an: Implementasi Tafsir Adabi Ijtima'i dalam Membaca Isu-Isu Kontemporer di Kalangan Pemuda - Supeno Supeno; Moh.Agil Nuruzzaman; Muslimatun Diana Muazaroh; Diana Elfiyatul Afifah; Sukirno Sukirno; Munahar Munahar; Nandipah Roa'zah (Eastasouth Institute, 2025)
The management of the Al-Qur'an literacy movement among youth involves implementing the Tafsir Adabi Ijtima'i approach, which interprets the Qur'an with a focus on social ethics and contemporary issues. This method, rooted in the works of scholars like Muhammad Abduh and others, uses accessible language and emphasizes the Qur'an’s relevance to current social challenges faced by young people. By integrating this interpretive style, the movement aims to enhance youths’ understanding of the Qur'an beyond ritual reading, fostering critical engagement with societal problems and encouraging active social responsibility. Studies show that such approaches can improve spiritual literacy and character education, although challenges remain in motivating consistent reading and comprehension among youth. The Tafsir Adabi Ijtima'i approach also aligns with transformative interpretations that connect religious values with social change, making it a strategic tool for empowering young Muslims in navigating modern realities. Overall, this model supports the development of a Qur'an-literate generation capable of addressing contemporary issues through informed and ethical perspectives rooted in Islamic teachings.